Development of silicon nanowire lab-on-chip microfluidics integrated biosensor for low concentration bio-molecules detection - Tijjani Adam, Shuwa (Universiti Malaysia Perlis (UniMAP), 2015)
Doctor of Philosophy in Nano electronic Engineering